Serving temperature viscosity measurements of nectar and honey-thick liquids - Garcia, Jane Mertz; Chambers, Edgar, IV; Matta, Ziad; Clark, Megan (My University, 2008)
This study reports the viscosity (thickness) of nectar- and honey-thick liquids measured at a typical serving temperature. Centipoise (cP) measurements were compared for three products (two starch and one gum-based thickener) mixed with five beverages that set for three time intervals (manufacturer recommended time to thicken, 10 and 30 minutes). The serving temperature of the cold beverages was 4º C (water, apple juice, orange juice, and milk), and the hot beverage (coffee) was measured at 70º C. Statistical analysis showed that all factors interacted with one another, meaning that the viscosity of a nectar- or honey-like liquid varies greatly depending on the type of thickening agent and beverage combination in relation to the amount of time its thickens. Simply Thick, the gum-based thickener, typically produced samples that were the least viscous but they maintained a more consistent level of thickness over time. Serving temperature results are contrasted with viscosity measurements collected at room temperature, showing variable thickening patterns especially related to the type of thickening agent.
Keywords: Dysphagia; Viscosity; Thickened beverages